2013
DOI: 10.1007/s11136-013-0441-6
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and sufficient causes of participation post-stroke: practical and philosophical perspectives

Abstract: Two treatable component causes of participation, walking capacity and mood, were identified; of these, only excellent walking capacity could be considered a sufficient cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 36 publications
2
52
1
2
Order By: Relevance
“…In fact, rating of health as poor or fair is sufficient to indicate service needs; rating of health as good or better is neither necessary nor sufficient to indicate no need, and this group would need to be specifically evaluated. (42) In addition, self-rated health used as single item, had a high specificity and a moderate to low sensitivity. Studies had shown that only 30% of seniors discharged from acute care fully recover to similar levels prior hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, rating of health as poor or fair is sufficient to indicate service needs; rating of health as good or better is neither necessary nor sufficient to indicate no need, and this group would need to be specifically evaluated. (42) In addition, self-rated health used as single item, had a high specificity and a moderate to low sensitivity. Studies had shown that only 30% of seniors discharged from acute care fully recover to similar levels prior hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recruitment for the original study was targeted to identify individuals with specific characteristics; 250 people with transtibial amputation from trauma, transtibial amputation from dysvascular causes, transfemoral amputation from trauma, transfemoral amputation from dysvascular causes, and bilateral amputation were sought.…”
Section: Methodsmentioning
confidence: 99%
“…The Prosthetic Limb Users Survey of Mobility (PLUS-M™) 24 was developed using the rigorous methods proposed by Reeve and colleagues 23 to fulfill the need for a brief, accurate, and clinically meaningful self-report mobility instrument specific to people with LLA. Development of a new instrument using contemporary standards was intended to address barriers to routine use, including relevance of items, administration burden, and ease of interpretation.…”
Section: Introductionmentioning
confidence: 99%